The effects of some protein-modifying reagents on the interaction of colicins A, E2, E3, and K with their respective Escherichia coli cell receptors - Smarda, J; Macholán, L (Journal of basic microbiology, 1988)
Colicins attach themselves--through specific protein-protein interactions--onto receptors in the outer membrane of sensitive bacterial cells. An attempt was made to analyze amino-acid groups and attractive forces involved in this interaction, following treatment of either colicins A, E2, E3 and K or sensitive bacteria with various physico-chemical factors and several protein-modifying reagents. The amounts of colicin bound were checked by a quantitative biological assay. Ionic conditions and specific spatial conformation of both colicin and its receptor molecules are crucial in their interaction and, hence, in the biological effect of colicin. Formaldehyde, naphthalene-diisocyanate and osmium tetroxide strongly inhibit the binding ability of all colicins tested. The results suggest that NH2 and SH groups are involved in their binding onto receptors; also, CH3S groups seem to be engaged in the attachment of colicins E2 and E3 and phenol-OH groups in that of colicin K. The possible involvement of further groups (NH, SH etc.) should be checked using more specific reagents. The attitude of colicins E2 and E3 to their common receptor Btu B protein is nearly, but not completely the same. Receptors for all colicins tested should be oxidized to achieve optimal interactions; obviously, carbonyl groups are produced and newly formed anions increase the negative load of bacterial surface. In agreement, reduction of at least colicins A and E3 enhances their receptor binding reactivity. The binding capacity of each receptor can be modulated by a set of amino acid reagents in a specific manner.
Keywords: oxid osmičelý; proteiny z Escherichia coli; formaldehyd; Receptors, Immunologic; Urea; koliciny; receptory imunologické; Propiolactone; ethanol; Escherichia coli; Escherichia coli Proteins; propiolakton; Ammonia; receptory buněčného povrchu; Colicins; močovina; Receptors, Cell Surface; Hydrogen-Ion Concentration; amoniak; Dansyl Compounds; Ethanol; koncentrace vodíkových iontů; Osmium Tetroxide; sloučeniny dansylu; Formaldehyde